Общак - это святое! - Барабошкин Александр (По фене о главном..., 2006)
Экземпляры: ф.2 (2008) / Инвентарный номер: 51912 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 24 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6-4